Modeling and experiment of slag corrosion on the lightweight alumina refractory with static magnetic field facing green metallurgy - Huang A.; Lian P.; Fu L.; Gu H.; Zou Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Electromagnetic field is applied widely in metallurgy and other high temperature processes, and affects the behavior of melts. The lightweight alumina based carbon free refractory is of importance for energy-saving, consumption reduction and high quality steel production, and the slag corrosion resistance is significant concerning its service life. Does electromagnetic field control the slag corrosion behavior on the lightweight alumina refractory? In this paper, a multi-field coupled model was established to describe the slag corrosion process in an electromagnetic field. The mathematical modeling in combination of experiments was applied to clarify slag corrosion behavior of lightweight alumina refractory in static magnetic field. The simulation results agree with that of the experiments, which means the proposed model is promising for slag corrosion modeling. The results show that the combination of the slag properties change, and electromagnetic damping caused by MHD (magnetohydrodynamics) effect can enhance the slag corrosion resistance by inhibiting slag penetration and promoting formation of a directional isolation layer, and be beneficial to high-quality clean steel production.